Play and learning materials in university model preschool: Exploring the availability and utilization - Wondimagegn Abebe; Yirgalem Alemu Keery (Atfaluna: Journal of Islamic Early Childhood Education, 2023)
This study explored the availability and utilization of play and learning materials in the Haromaya University Model Preschool, Ethiopia. In doing so, a qualitative case study design was employed. Data were generated from five chosen teaching staff of the model preschools purposively traced by the researchers. Interview protocol and observation checklist were utilized as a data-gathering tool. To comprehend the phenomenon, the researcher used thematic analysis. The study's findings were illustrated with 3 major themes and 8 sub-themes. There are average materials available for play and education in the model preschool. Teachers utilize play and learning materials to introduce new concepts, reinforce learning, promote socio-emotional development, and promote creativity. Several factors determine the usage of play materials for learning: economy, perception, and attitude of teachers, and educational qualification of teacher topping the list. In conclusion, play and learning materials are essential for preschool children's development. They help children learn engagingly, promote creativity and problem-solving skills, and provide opportunities to explore, learn, and grow. However, the level of play and learning materials is different than expected. It can create a disparity in the quality of education that children receive. To address this issue, increased funding for preschool programs, provision of training for preschool teachers on using play and learning materials effectively, and awareness creation about the importance of play and learning materials should be in place.